Mongolia : First and Second Reviews Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria, Extension of Arrangement and Rephasing of Purchases. (IMF Staff Country Reports; Country Report ;, 2003)
Mongolia has performed commendably under the Poverty Reduction Growth Facility arrangements. Executive Directors commended the prudent macroeconomic policies, low inflation, and reduction in vulnerability. They stressed the need to strengthen the fiscal position, improve economic governance, pursue prudent monetary and external debt management policies, and maintain an open trade and investment regime. They agreed that Mongolia's Economic Growth Support and Poverty Reduction Strategy (EGSPRS) provides a sound basis for IMF's concessional financial assistance, and approved further finance assistance.